2006
DOI: 10.1080/08923970600927447
|View full text |Cite
|
Sign up to set email alerts
|

Design of a New Line in Treatment of Experimental Rheumatoid Arthritis by Artesunate

Abstract: This study was aimed to evaluate the therapeutic potency of a new antimalarial drug, artesunate, in an experimental model of rheumatoid arthritis. Collagen-induced arthritis (CIA) was induced in Lewis rats.The intraperitoneally administration of artesunate (ARS) and methotrexate (MTX) were started on day 25 postimmunization and continued until final assessment on day 35. During this period, clinical examination was intermittent. The anticollagen type II antibody (CII Ab) and nitric oxide synthesis were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…It was reported that artemisinin inhibited NF-κB-mediated iNOS expression and NO synthesis [30] . Owing to this property, several artemisinin derivatives were found to be effective for treating experimental arthritis and lupus nephritis in animal models, however, their bioactivity is limited [31][32][33][34] . SM905 is a novel artemisinin derivative with promising immunosuppressive activity in vitro and in vivo [26] , and oral administration of SM905 induced suppression of collagen-induced arthritis in mice [27] .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that artemisinin inhibited NF-κB-mediated iNOS expression and NO synthesis [30] . Owing to this property, several artemisinin derivatives were found to be effective for treating experimental arthritis and lupus nephritis in animal models, however, their bioactivity is limited [31][32][33][34] . SM905 is a novel artemisinin derivative with promising immunosuppressive activity in vitro and in vivo [26] , and oral administration of SM905 induced suppression of collagen-induced arthritis in mice [27] .…”
Section: Discussionmentioning
confidence: 99%
“…By the addition of a hemisuccinate group, artesunate is more water-soluble with greater bioavailability and better pharmacological profile (Newton et al 2000). Apart from its effective anti-malarial actions, artesunate has promising anti-inflammatory potential in animal models of rheumatoid arthritis (Mirshafiey et al 2006;Li et al 2013), systemic lupus erythematosus (Jin et al 2009) and bacteria-induced sepsis (Li et al 2010;Jiang et al 2011). Recently, studies have demonstrated broad anti-inflammatory and anti-oxidative properties of artesunate in experimental allergic asthma (Cheng et al 2011;Ho et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The paws and knees were then removed for histopathological assay. Macroscopic scoring system using a scale from 0 to 4 for each paw was used to evaluate arthritis [7]. On day 35, animals were anesthetized and killed.…”
Section: Methodsmentioning
confidence: 99%
“…After fixation and decalcification of paws and knees, they stained with hematoxylin and eosin for histological examination. Joint damage was assessed as previously described [7]. According to the severity of damage, joint erosion was graded on a scale of 0 -3 for each limb.…”
Section: Methodsmentioning
confidence: 99%